Rapid onset of action and reduced nasal hyperreactivity: new targets in allergic rhinitis management. Issue 1 (25th June 2018) - Bachert, C.; Bousquet, J.; Hellings, P.
Abstract: Background: This article summarizes a EUFOREA symposium, presented during the European Rhinology Research Forum in Brussels (9–10 November 2017; https://www.rhinologyresearch.eu/ ) which focused on novel pathways and therapeutic approaches in allergic rhinitis (AR). Main body: AR remains under‐diagnosed, under‐estimated and under‐treated. A key component in understanding the AR landscape has been the realization of a significant mismatch between how physicians instruct AR patients to manage their disease and what AR patients actually do in real life. Data from the Allergy Diary (developed by MACVIA ARIA) showed that AR patients take their medication prn, rapidly switch treatments, often experience poor control, use multiple therapies and stop treatment when symptoms are controlled. Better control of AR may be achievable by using an AR treatment which has a rapid onset of action and which effectively targets breakthrough symptoms. Indeed, AR patients report complete symptom relief, lack of breakthrough symptoms, rapid onset of action, safety and use on an 'as needed' basis as key targets for new nasal sprays. MP‐AzeFlu comprises intranasal azelastine and fluticasone propionate (FP) in a novel formulation delivered in a single device. It is the first AR treatment to break the 5 min onset of action threshold and provides clinically relevant symptom relief in 15 min, much faster than that noted for FP + oral loratadine. MP‐AzeFlu also significantly reduces nasal hyperresponsiveness (NHR) which may be responsible for the breakthrough symptoms frequently reported by AR patients. Mechanisms underlying MP‐AzeFlu's effect include inhibition of mast cell degranulation, stabilization of the mucosal barrier, synergistic inhibition of inflammatory cell recruitment and a unique desensitization of sensory neurons expressing the transient receptor potential A1 and V1 channels. Conclusion: With the most rapid onset of action and onset of clinically‐relevant effect of any AR medication currently available, and proven efficacy in the treatment of NHR, MP‐AzeFlu is an AR treatment which provides what patients want, and fits how patients manage their AR in real life.